Wybrane czynniki wpływające na decyzje wyborców w elekcji parlamentarnej w 2011 roku - Alberski, Robert (Political Preferences, 2012)
This part of the report describes two problems, which were included in both question- naires from 2010 and 2011. First issue asks about the time, when the voter made his decision for which political option he would vote for. Second problem concerns about factors, which determines for which candidate, he would choose. In 2010 we research this problem in refer- ence to Local election. This time our questions refers to candidates in elections to Sejm and Senate. We wanted to verify the trends we observed in Local and Presidential elections in Par- liamentary election. Obtained data in great part confirms conclusions from previous researches. Once again it turned out that majority voters was sure of their political preferences long before the voting, so they weren't susceptible to electioneering. Another observation, which was con- firm by the researches made in the end of 2011, relates to limited effectiveness of electioneering on voter. Our researches don't show any greater differences in factors, by which voter made his decision for which candidate he vote for in Parliamentary election.